Wheat production by system of wheat intensification technique - Suryavanshi, P; Singh, Y V (Indian Farming, 2018)
System of wheat intensification is intended to help small-and marginalfarmers with limited resources to produce higher yield with increased monetary returns. It is a real bottom up technology which is adopted on a large-scale by farmers after being promoted by NGO’s and other government agencies. Future strategy should conduct extensive field research in agricultural universities and research stations so that new interventions can be done to make this technology more remunerative for resource poor farmers in a sustainable manner.